Nivel de estrés y rendimiento académico de los estudiantes de la facultad de enfermería, UNT Sede Huamachuco - Acosta Rebaza, Tania Milagros (2015)
This study of Quantitative Research descriptive-correlational cross-section was performed in order to identify to what extent the level of stress is related to academic performance of students of the School of Nursing Office - Huamachuco 2014. The sample it consisted of 80 students, selected according to the inclusion criteria. To collect data two instruments were used: the academic stress questionnaire and the data collection sheet for the weighted average. The results are presented in tables of single and double entry with numerical and percentage data and statistical graphics. It was found that 67.5% of students had a low level of stress, and 32.5% had a medium level of stress. In addition, 80.0% of students presented a good level of academic performance, while 11.3% had a regular academic performance level; and 8.8% of students had a poor academic performance level; Finally, analysis of the relationship between the study variables was performed using the chi-square test (x2), obtaining a 0.6801con a probability of 0.7117, still is not highly significant, meaning that there is no relationship between the variables.